Bibliometric Mapping of Flash Flood and Emergency Response Research: The Position of Public Response - Vania Putri Ardini; Iip Permana (YASIN, 2026)
Public response to emergency measures is critical to the effectiveness of flash flood disaster management because these events occur suddenly and provide only a limited warning period. Although research on disaster emergency response has expanded, bibliometric evidence concerning the position of public response within the scientific literature on flash floods remains limited. This study maps the thematic structure and relative position of public response in flash flood and emergency response research. A quantitative bibliometric approach was employed using 991 documents retrieved from Google Scholar through a Boolean search for “flash flood,” “public response,” and “emergency response” in article titles, abstracts, and keywords. The documents were exported in CSV format and analyzed using VOSviewer 1.6.21 through network and density visualizations. The findings indicate that “flash flood” was closely connected to the core themes of emergency response, including disaster, case study, emergency service, disaster management, policy, landslide, and disaster risk reduction, with 63 occurrences, 141 links, and a total link strength of 395. By contrast, “public response” occupied a peripheral position and displayed substantially weaker connections within the network. Density visualization further showed that the most concentrated research areas surrounded the terms “disaster” and “policy,” whereas “flash flood” was positioned at the boundary of this high-density area. The separate clustering of “flash flood” and “flash flooding” also indicates terminological inconsistency across the analyzed literature. These findings demonstrate that flash flood research remains dominated by operational, institutional, and policy-oriented dimensions of emergency response, while public responses to emergency directives remain underexplored. This study contributes to the identification of thematic gaps and highlights the need for standardized terminology and further research on how communities interpret and respond to emergency instructions during flash flood events.